CREATING CUSTOMER RETENTION THROUGH FACILITIES, COMPLAINT HANDLING, TRUST, COMPANY IMAGE AND CUSTOMER INCENTIVES AT BMT AMANAH UMMAH KARTASURA, SUKOHARJO - Istiatin, Istiatin; Marwati, Fithri (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2021)
This study has purpose to determine and analyze the effect of Company Image, Customer Incentives, Trust, Complaints Handling, and Facilities on Costumer Retention at BMT Amanah Ummah Kartasura. The research method applied in this study was a quantitative descriptive research design. This study used a population of 1,500 respondents. In determining the sample size, this study used the Slovin formula. Based on the results of calculation, the number of samples in this study was 100 respondents. The sampling technique was carried out using incidental sampling. The data collection was done using a questionnaire. The data analysis technique in this study was statistical analysis consists of multiple linear regression test, F test, t test and the coefficient of determination. The results showed that the Company Image, Customer Incentives, Trust, Complaint Handling, and Facilities simultaneously had a significant effect on Customer Retention at BMT Amanah Ummah Kartasura. Partially, it was found that Company Image and Customer Incentives do not have a positive and significant effect on Customer Retention at BMT Amanah Ummah in Kartasura. Meanwhile, Trust, Complain Handling, and Facilities have a positive and significant effect on Customer Retention at BMT Amanah Ummah in Kartasura. The coefficient of determination or the contribution of the variables of Company Image, Customer Incentives, Trust, Complain Handling, and Facilities on Customer Retention at BMT Amanah Ummah Kartasura was 43.1%. This study suggested that BMT Amanah Ummah should continue to improve and pay attention to the factors that affect the Customer Retention, such as Company Image, Customer Incentives, Trust, Complain Handling, and Facilities. Keywords: Customer Retention, Trust, Complaint Handling, Facility, Company Image, BMT Amanah Ummah